ANALYSIS OF YIELD GAP IN WHEAT - Thakare, Sandip Shridhar; Agam, Priyanka Ashokrao; Ulemale, Deepak Hiroji; Chirade, Pritam Nagorao (Journal of Cereal Research, 2025)
In this study, an attempt has been made to study the analysis of yield gap in wheat. The primary data on input used and there upon costs were collected from two tehsils viz. Amravati and Morshi, while the secondary data on area, production and productivity was pertained to the periods 1983-84 to 2012-13 was collected from various Government publications. The study reveals that the area under wheat in Amravati has increased by 17.29 per cent per annum during period III while at overall level it shows significant growth. The yield gap analysis shows that at overall, yield Gap I i.e. difference between potential yield and demonstration plot yield worked out to be 879 kg/ha and yield Gap II i.e. demonstration plot yield and farmers yield was 579 kg/ha. The highest total yield gap was recorded in large farmers (830 kg/ha) while lowest in small farmers (508 kg/ha). Magnitude and Direction of yield gap shows that the yield gap is increased at increasing rate. The path analysis measured the direct and indirect effect of input gaps on yield gaps explained that the total effect of human labour (0.613) was found to be highest in small farmers while bullock labour (0.371), machine labour (0.431) found to be highest in small groups farmers. At overall level total effect of seed and fertilizer (0.871) and (0.337) respectively. The manure and plant protection effect is (0.306) and (0.410). The total area effect highest in medium size group of farmers.